UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI MODEL PEMBELAJARAN LANGSUNG SISWA KELAS I SD NEGERI 001 UKUI SATU - Nurhamimah ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research was motivated by the low results of social studies students of class I SD Negeri 001 Ukui Satu. Of the 20 students only 10 students who completed study results. This study aims to improve learning outcomes IPS through direct learning model application. This research is a class act, carried out by two cycles. Data of this research focuses on improving student learning outcomes IPS. IPS expressed increasing learning outcomes based on initial score of student learning outcomes by 65 to 50% the percentage of completeness, the first cycle increased with the acquisition of learning outcomes at 69.25 with the percentage of completeness 70%. And the second cycle learning outcomes increased with the acquisition of 74.5 to 85% the percentage of completeness. Based on this it can be concluded that the application of direct learning model can improve student learning outcomes IPS 001 first grade of SD Negeri 001 Ukui Satu.